SAT0123 TREATMENT SATISFACTION, EXPECTATIONS, PATIENT PREFERENCES AND CHARACTERISTICS, INCLUDING DIGITAL HEALTH LITERACY (DHL), AND THE IMPACT OF SUBOPTIMAL DISEASE CONTROL IN A LARGE INTERNATIONAL COHORT OF PATIENTS WITH RHEUMATOID ARTHRITIS (RA): THE SENSE STUDY. (2nd June 2020) - Taylor, P. C.; Ancuta, C.; Nagy, O.; Delavega, M.; Gordeev, A.; Jankova, R.; Kalyoncu, U.; Lagunes-Galindo, I.; Morovic-Vergles, J.; Peixoto Gu e Silva de Souza, M.; Rojkovich, B.; Sidiropoulos, P.; et al.
Abstract : Background: Patient characteristics, their treatment preferences and goals are important determinants of treatment success in rheumatoid arthritis (RA). Objectives: SENSE study aimed at assessing the impact of inadequate response to disease-modifying anti-rheumatic drugs on disease outcomes, and analyze their attitude, their treatment and disease. Methods: Non-interventional, cross-sectional study conducted in 18 countries in Europe, Asia, and America. Adult RA patients with moderate/high disease activity were eligible. Patient satisfaction was assessed by Treatment Satisfaction Questionnaire for Medication, Version 1.4 (TSQM v1.4). Treatment adherence, patient preferences, and expectations were evaluated by visual analog scale. eHealth Literacy Scale was employed for evaluating DHL. Work Productivity and Activity Impairment Questionnaire-Rheumatoid Arthritis, v2.0 (WPAI-RA) was used to assess workability and patient documentation for healthcare resource utilization (HRU). Results: 1624 patients were included in this analysis; most were female (84.2%), middle-aged, and had a mean (standard deviation [SD]) disease duration of 10.5 (9.3) years. 11.9% of the patients had retired early and 6.0% were unemployed due to RA. Mean (SD) total WPAI-RA score was 55.1% (26.7). In the previous 3 months, the mean (SD) number of healthcare professional and emergency room visits were 2.2 (2.5) and 1.6 (1.3), respectively. Mean (SD) TSQM v1.4 global satisfaction subscore was 60.9 (20.9), with only 13.5% reporting good treatment satisfaction (TSQM global ≥80). The leading treatment expectations were 'general improvement of arthritis', 'less joint pain', and 'lasting relief of RA symptoms, ' with mean (SD) scores of 5.7 (1.6–1.7) for each. 60.7% of patients preferred oral administration and 31.3% preferred not to use drug combinations for RA. Preferred time to effect was predominantly 'up to one week' (71.1%). Least frequently side effects rated 'acceptable' were 'increased risk for malignancies' (3.5%) and 'increased risk for cardiovascular diseases' (3.3%). Most patients (67.4%) had poor DHL. Good adherence (in 87.4% of patients) was significantly associated with lower levels of joint pain. Conclusion: Suboptimal disease control has a significant impact on satisfaction, workability, and HRU. Our results can support shared decision-making when setting RA treatment strategy. Disclosure of Interests: Peter C. Taylor Grant/research support from: Celgene, Eli Lilly and Company, Galapagos, and Gilead, Consultant of: AbbVie, Biogen, Eli Lilly and Company, Fresenius, Galapagos, Gilead, GlaxoSmithKline, Janssen, Nordic Pharma, Pfizer Roche, and UCB, CODRINA ANCUTA Consultant of: AbbVie, Pfizer, Roche, Novartis, UCB, Ewopharma, Merck Sharpe and Dohme, and Eli Lilly, Speakers bureau: AbbVie, Pfizer, Roche, Novartis, UCB, Ewopharma, Merck Sharpe and Dohme, and Eli Lilly, Orsolya Nagy Shareholder of: AbbVie, Employee of: AbbVie, Maria DeLaVega: None declared, Andrey Gordeev Speakers bureau: AbbVie, Eli Lilly, Pfizer, Sanofi, Bristol-Myers Squibb, Merck Sharpe and Dohme, Roche, and UCB., Radka Jankova Speakers bureau: AbbVie, Eli Lilly, Pfizer, Sanofi, Bristol-Myers Squibb, Merck Sharpe and Dohme, Roche, and UCB, Umut Kalyoncu Consultant of: AbbVie, Amgen, Eli Lilly, Janssen, Novartis, Pfizer, Roche, and UCB., Speakers bureau: AbbVie, Amgen, Eli Lilly, Janssen, Novartis, Pfizer, Roche, and UCB., Ivan Lagunes-Galindo Shareholder of: AbbVie Inc., Employee of: AbbVie Inc., Jadranka Morovic-Vergles Speakers bureau: Abbvie., Roche, MSD, Eli Lilly, Pfizer, Mylan, Amgen, Fresenius Kabi, Mariana Peixoto GU e Silva de Souza Grant/research support from: AbbVie, UCB, Bristol-Myers Squibb, Pfizer, and GSK, Consultant of: AbbVie, Roche, UCB, Pfizer, and Jansen, Speakers bureau: AbbVie, Roche, UCB, Pfizer, and Jansen, Bernadette Rojkovich: None declared, Prodromos Sidiropoulos: None declared, Atsushi Kawakami: None declared